2009
DOI: 10.1029/2008jf001075
|View full text |Cite
|
Sign up to set email alerts
|

Discrete element simulation of the Jiufengershan rock‐and‐soil avalanche triggered by the 1999 Chi‐Chi earthquake, Taiwan

Abstract: [1] We present Contact Dynamics discrete element simulations of the earthquaketriggered Jiufengershan avalanche, which mobilized a 60 m thick, 1.5 km long sedimentary layer, dipping $22°SE toward a valley. The dynamic behavior of the avalanche is simulated under different assumptions about rock behavior, water table height, and boundary shear strength. Additionally, seismic shaking is introduced using strong motion records from nearby stations. We assume that seismic shaking generates shearing and frictional h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…The intensity of particle agitation can be quantified by the vibrational and rotational granular temperatures in Figure 11a. In addition, the fracturing and fragmentation of rock also involve intense energy dissipations, together with boosts of granular momentum for some rock fragments, leading to the increase of landslide mobility ( According to Campbell et al (1995), Strom (1999), and Chang and Taboada (2009), even though intense shearing exists within a completely fragmented slope, the landslide debris deposit exhibits approximately the same strata order as its original stratigraphic structure in the source mountainside after a long runout. This feature can also be well illustrated in the current study on the dynamic fragmentation of an initially intact rock slope ( Figure 5).…”
Section: Dynamic Rock Fragmentation and Shear Resistance Reductionmentioning
confidence: 99%
“…The intensity of particle agitation can be quantified by the vibrational and rotational granular temperatures in Figure 11a. In addition, the fracturing and fragmentation of rock also involve intense energy dissipations, together with boosts of granular momentum for some rock fragments, leading to the increase of landslide mobility ( According to Campbell et al (1995), Strom (1999), and Chang and Taboada (2009), even though intense shearing exists within a completely fragmented slope, the landslide debris deposit exhibits approximately the same strata order as its original stratigraphic structure in the source mountainside after a long runout. This feature can also be well illustrated in the current study on the dynamic fragmentation of an initially intact rock slope ( Figure 5).…”
Section: Dynamic Rock Fragmentation and Shear Resistance Reductionmentioning
confidence: 99%
“…On the 21th September 1999, the Chi-Chi earthquake in Taiwan triggered a major landslide in the Tsaoling area [Hung (2000); Chang and Taboada (2009)]. The detached landslide mass had a volume about 125 × 10 6 m 3 .…”
Section: A Seismic Signal From Station Chy080 At Chi-chimentioning
confidence: 99%
“…However, many researchers have reported that the behavior of geo-materials can still be adequately captured by DEM despite these simplifications (Calvetti and Emeriault, [11]; Potyondy and Cundall, [12]; Cui and O'Sullivan, [13]; Cho et al, [14]; Wang and Leung, [15]; Hsieh et al, [16], Schopfer et al [17]). In addition, the DEM has been successfully applied to many areas of engineering, such as soil mechanics, rock engineering, tunneling, and landslide evaluation (Hentz et al, [18]; Utili and Nova, [19]; Sitharam et al, [20]; Chang and Taboada, [21]). …”
Section: Introductionmentioning
confidence: 98%